2016
DOI: 10.3989/gya.0641152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dry salting on flavonoid profile and antioxidant capacity of Algerian olive cultivars

Abstract: SUMMARY:This study investigated the changes in the flavonoid profile and antioxidant capacity of five olive cultivars after dry salting. The antioxidant activity was determined using ferric reducing ability power (FRAP), oxygen radical absorbance capacity (ORAC), and β-carotene bleaching assays. The results showed that the effects of dry salting on the analyzed parameters were significant (P<0.05). It caused a decrease in total flavonoids with a loss rate of 55%. The HPLC analysis of extracts revealed the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…(2010) also examined commercial Greek table olives for their oleuropein and hydroxytyrosol content and found compounds with concentrations of 800 mg kg −1 and 350 mg kg −1 respectively in the Throuba Thassos variety debittered in dry salt . Soufi et al . investigated the changes in the flavonoid profile of five olive cultivars after dry salting.…”
Section: Resultsmentioning
confidence: 99%
“…(2010) also examined commercial Greek table olives for their oleuropein and hydroxytyrosol content and found compounds with concentrations of 800 mg kg −1 and 350 mg kg −1 respectively in the Throuba Thassos variety debittered in dry salt . Soufi et al . investigated the changes in the flavonoid profile of five olive cultivars after dry salting.…”
Section: Resultsmentioning
confidence: 99%
“…EOGM had the highest concentrations of polyphenols (1884.66 mg GAE/kg) and ortho-diphenols (271.39 mg CAE/mL) whereas EOGB had the lowest concentration of polyphenols (1746.5 mg GAE/kg), and EOBM had the lowest concentration of ortho-diphenols (Table 1). The phenolic content of olives decreases during ripening (Soufi et al, 2016). Diversity in phenolic content is due to the influence of cultivar, ripening, and processing method.…”
Section: Polyphenols and Ortho-diphenolsmentioning
confidence: 99%
“…This condition might have caused the release of compounds responsible for neuritogenic activities from the tissue. Soufi, Romero, Motilva, Gaya, and Louaileche (2016) reported that salting decreased the antioxidant activity of olive because of the loss of flavonoid compounds. Salting of Ulva rotundata with 25% NaCl and storing at RT decreased the yield of ulvan extraction (Robic et al, 2007).…”
Section: Effects Of Drying Treatments On Neuritogenic Activitiesmentioning
confidence: 99%